Identities Through Time: An Exploration of Identity Change as a Cause of Desistance. (2nd January 2016) - Rocque, Michael; Posick, Chad; Paternoster, Ray
Abstract : Research examining desistance from crime (the process of decreasing offending over time) has increased over the last 20 years. However, many explanations of desistance remain somewhat exploratory. One theory in particular that is becoming more prominent includes the idea that desistance is caused by a change in identity (e.g. from deviant to pro-social). While qualitative support has been found for this proposition, prospective quantitative studies have not been conducted on this theory. This study addresses that gap by examining how pro-social identities change over time and whether these changes correspond to desistance from crime. The results of growth curve models indicate that pro-social identity increases over time and is a robust predictor of criminal behavior over the life course. These results offer support to identity theories of desistance and also provide important information for correctional programming.